Determination of lipl32 epitope of leptospirosis via in silico method and elisa - Mohd Iskandar Jumat (2018)
Leptospirosis is a predominant zoonotic disease caused by a pathogenic strain of L. interrogans. Diagnosis of leptospirosis includes microscopic agglutination test (MAT assay) and enzyme-linked immunosorbent (ELISA) which utilizes 6 designated outer membrane protein (OMP). Of these LipL32 is found to be most useful. However current prediction of the Lipl32 epitope has been largely depend on empirical rather than in silica methods. In addition, currently no known reports of LipL32 epitope prediction using more than one bioinformatic algorithm. In this, study, full length Lipl32 protein was analyzed using three bioinformatic algorithms, which were the Kyte and Doolittle hydropathy scale, the recognition factor and the Kolaskar and Tangaokar propensity scale. The application of these three algorithm overlaps resulted in the recognition of three antigenic regions namely the Nrlipl32 (amino acid sequence Ala21-Glu122), the intermediate Lipl32 (amino acid sequence Prp144-G lu]11) and the Crlipl32 (amino acid sequence Thr200-Ser261) fragments. Investigation for sensitivity and specificity among the fragments via EUSA indicated that CrLipL32 has the highest sensitivity (IgM 73.3% and IgG 60%) indicating to be the immunodominant epitope of Lipl32. In conclusion, this study demonstrated that Crlipl32 is the immunodominant fragment of Lipl32.